2011
DOI: 10.1007/s11605-010-1391-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Combined Intraoperative Ablation and Resection for Colorectal Liver Metastases: An International, Multi-institutional Analysis

Abstract: Combined resection and ablation is associated with long-term-survival in a subset of patients; however, recurrence is common. The number of lesions ablated increases risk of intrahepatic recurrence but does not impact overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
(57 reference statements)
1
32
0
Order By: Relevance
“…The use of a single-stage strategy of resection combined with ablation was previously reported mostly in single-centre studies with small numbers 33 -36 . Most of these studies used radiofrequency ablation as the primary method of ablation versus a microwave technique, which is more efficacious with larger lesions and around areas of heat-sink concern 37 . The present large series adds to the data on combined resection with MWA, and provides longer follow-up than described previously 38 , leading to more robust survival and recurrence analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a single-stage strategy of resection combined with ablation was previously reported mostly in single-centre studies with small numbers 33 -36 . Most of these studies used radiofrequency ablation as the primary method of ablation versus a microwave technique, which is more efficacious with larger lesions and around areas of heat-sink concern 37 . The present large series adds to the data on combined resection with MWA, and provides longer follow-up than described previously 38 , leading to more robust survival and recurrence analyses.…”
Section: Discussionmentioning
confidence: 99%
“…13 Morbidity similarly remains a problem after hepatic resection, with surgery-related morbidity being documented in 20% to 40% of patients after surgery. 7,16,22 Several previous groups have proposed prediction rules based on postoperative laboratory values to identify patients at the highest risk of mortality after liver resection. 13,14 Other groups have suggested that biochemical data might even help to recognize surgery-related complications early during the postoperative course.…”
Section: Discussionmentioning
confidence: 99%
“…It is well stablished in the area of digestive surgery that surgical resection is the most effective treatment for isolated liver metastasis in patients with colorectal cancer 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, patients undergoing simultaneous resections could expect a short duration of surgery and postoperative hospitalization as well as less blood loss during surgery 13 . Although the treatment for patients with synchronous colorectal cancer liver metastases remains controversial, surgical resection of both the primary tumor and liver metastases is the only option offering a potential cure 13 .…”
Section: Discussionmentioning
confidence: 99%